Colonial scholars and anti-colonial agents: politics of academic knowledge production between the West Indies and London in the mid-20th century - Cramer, Meta (2023)
Abstract: This paper analyses the socio-spatial entanglement of West Indian anti-colonial knowledge production in the mid-20th century existing between London and the Caribbean. This is interpreted as a case of the paradoxical politics of academic knowledge production in that British imperial policies that were constraining knowledge production in the West Indies were also seen as facilitating anti-colonial awareness and work in London by West Indian actors. Research demonstrating the importance of the metropole as a meeting place for global anti-colonial actors is complemented by shifting the focus to the entangled space between London and the West Indies. This article comparatively analyses the academic politics of the British Colonial Office – a spatial dislocation of knowledge production away from the West Indies – and its perception and challenge by Caribbean intellectuals who were temporarily based in London. The analysis builds on contributions by C.L.R. James and S. Wynter and their reflections on the institutionalisation of research in the West Indies and their experiences in London. Overall, I emphasise a relational and symmetrising analysis of knowledge production in imperial contexts that accounts for the entanglement of imperial politics in the metropole and the colonies, and the perception and potential use of these political entanglements by actors in and from colonial contexts